Imaging results from the legacy Giant Metrewave Radio Telescope Galaxy Cluster Key Project. Issue 3 (11th August 2021) - George, Lijo T; Kale, Ruta; Wadadekar, Yogesh
ABSTRACT: We have used archival Giant Metrewave Radio Telescope (GMRT) data to image and study 39 galaxy clusters. These observations were made as part of the GMRT Key Project on galaxy clusters between 2001 and 2004. The observations presented in this sample include 14 observations at 610 MHz, 29 at 325 MHz, and three at 244 MHz covering a redshift range of 0.02–0.62. Multifrequency observations were made for eight clusters. We analysed the clusters using the spam processing software and detected the presence of radio halo emission for the first time in the clusters RXC J0510−0801 and RXC J2211.7−0349. We also confirmed the presence of extended emission in 11 clusters which were known from the literature. In clusters where haloes were not detected, upper limits were placed using our own semi-automated program. We plot our detections and non-detections on the empirical L X − P 1.4 and M 500 − P 1.4 relation in radio halo clusters and discuss the results. The best fits follow a power law of the form L_500 P_1.4^1.82 and M_500 P_1.4^3.001 which is in accordance with the best estimates in the literature.